Right Heart Morphology of Candidate Patients for Transcatheter Tricuspid Valve Interventions - Khalique, Omar K.; Jelnin, Vladimir; Hueske, Andreas; Lawlor, Mathew; Leon, Martin B.; Kodali, Susheel K.; Akkoc, Deniz; Pettway, Eriq; Hahn, Rebecca T.; Hamid, Nadira B.; George, Isaac; Patel, Amisha; et al. (Cardiovascular engineering and technology, 2022)
Purpose This study quantitatively evaluated the phasic right heart morphology of candidate patients for a transcatheter tricuspid valve intervention (N=32) and of subjects with trace to no tricuspid regurgitation ( N = 14). Methods Cardiac computed tomography angiography (CCTA) and transthoracic/transesophageal echocardiography (TTE/TEE) images were analyzed using dedicated research and clinical software. Using CCTA, the phasic right atrial and ventricular volumes, annulus dimensions, annulus-to-right coronary artery (RCA) distances, circumferential topography of the annular tissue shelf, vena cava dimensions (inferior and superior), vena cava positions, axis angles, and annular excursions were quantified. Using TTE/TEE, leaflet geometry, regurgitation, hemodynamics, and heart function were quantified. Measurements within and between groups were quantitatively compared with regression analyses to explore relationships between right heart features. Results The phasic position and orientation of the vena cava and the circumferential topography of the annular tissue shelf were quantitatively presented for the first time. The candidate patient group exhibited greater chamber dimensions, enlarged vena cava, distended vena cava positions, positional shallowing of the annular tissue shelf, geometric annular distortion, leaflet distention, moderate or greater regurgitation, and impaired ventricular function. Atrial volume correlated strongly with directional vena cava positions as well as with annular dimensions. Annulus-to-RCA distances and annular excursions were comparable between groups. Conclusions This study provides new and further insight to the right heart morphology and functional characteristics of candidate patients for a transcatheter tricuspid valve intervention. These data provide a platform from which these patients can continue to be better understood for further improving transcatheter system design and use.